THE MAIN FORMATS OF INTERNATIONAL COOPERATION WITHIN THE FRAMEWORK OF MULTELATERAL DIPLOMACY - Kunina Irina (International Journal of Innovative Technologies in Social Science, 2025)
A comprehensive study of the formation and development of the institute of multilateral diplomacy, as well as the mechanisms and methods of its implementation, is becoming particularly relevant at the present stage. Due to the increasing complexity of global political processes and the formation of a new world order, many scientists, public figures and politicians today dispute the value of multilateralism, which negatively affects the development of its institutions. The purpose of this article is to study multilateral diplomacy in the context of revealing the main formats of international interaction within the framework of this type of diplomacy. In theory, multilateral diplomacy is guided by some key principles of international order. In practice, multilateral diplomacy is the main instrument of cooperation in the search for agreed solutions, as well as the implementation of the political goals of certain participating States. This kind of diplomacy requires a serious modernization of diplomatic structures, tools and methods.